The complex variable reproducing kernel particle method for elasto-plasticity problems - Chen, Li; Cheng, YuMin (Science China. Physics, mechanics & astronomy, 2010)
On the basis of reproducing kernel particle method (RKPM), using complex variable theory, the complex variable reproducing kernel particle method (CVRKPM) is discussed in this paper. The advantage of the CVRKPM is that the correction function of a two-dimensional problem is formed with one-dimensional basis function when the shape function is formed. Then the CVRKPM is applied to solve two-dimensional elasto-plasticity problems. The Galerkin weak form is employed to obtain the discretized system equation, the penalty method is used to apply the essential boundary conditions. And then, the CVRKPM for two-dimensional elasto-plasticity problems is formed, the corresponding formulae are obtained, and the Newton-Raphson method is used in the numerical implementation. Three numerical examples are given to show that this method in this paper is effective for elasto-plasticity analysis.